Single Fixed-Time Post-Cervical Insemination in Gilts with Buserelin - Andrés Suárez-Usbeck; Olga Mitjana; María Teresa Tejedor; Cristina Bonastre; Jorge Sistac; Antonio Ubiergo; María Victoria Falceto (Animals, 2021)
Current protocols for gilts recommend the deposit of multiple semen doses in the cervix each 12–24 h after estrus detection. Our objectives were: (1) to determine the effect of buserelin and a single fixed-time artificial insemination using the new post-cervical artificial insemination technique (FTAI-PCAI) on reproductive and productive performance in gilts, and (2) to compare this protocol with conventional estrus detection and double PCAI without hormonal induction. In the control group (C; n = 240), gilts were inseminated twice (8 and 12 h from estrus onset). Gilts in the treatment group (T; n = 226) received buserelin (10 μg, intramuscular) 120 h after altrenogest treatment (18 d) and one single PCAI 30–33 h after buserelin administration. The groups did not differ in reproductive and production performance (p > 0.05). The T group showed greater piglet birth weight and shorter estrus duration (p < 0.001). Delivery batch length differed significantly depending on the season (p < 0.05); the shortest length corresponded to autumn. Both groups only differed significantly in spring (p = 0.018), with a shorter length in the T group. This new FTAI-PCAI protocol with buserelin is recommended in gilts, helping with optimization of genetic diffusion, boars, and semen doses.